Despite huge investment to contain AMR, recent reports of increased occurrence of superbugs are terrifying - BH Gulumbe (Sri Lankan Journal of Infectious Diseases, 2018)
Antimicrobial resistance (AMR) which is considered a significant global health crisis continues to evolve and spread across the globe. If no adequate strategies are put in place to halt its rapid spread, routine surgical and medical procedures would become impossible without effective antimicrobials. By the year 2050, AMR is estimated to cost 10 million lives and about US$100 trillion annually.  Growing concerns due to the escalating spread of multidrug resistant organisms have forced the World Health Organisation (WHO), the Centre for Disease Control and Prevention (CDC), European Commission of the EU, the UK Department of Health and the African Academy of Sciences to put strategies against AMR in place.  However, despite efforts to halt AMR, recent reports show disturbing trends of difficult-to-treat deadly infections including gonorrhoea, typhoid, pneumonia, influenza, HIV, malaria and tuberculosis. This article bolsters the need for a comprehensive, real-time and improved surveillance of multidrug resistant organisms, sustained and coordinated action against AMR, development of new antibiotics and vaccines, prevention and control of diseases, improved sanitation and hygiene, sustained research, development of rapid diagnostics as well as provision of affordable and accessible health services.